PENGEMBANGAN E-MODUL BERBASIS ICARE BERBANTUAN FLIPPINGBOOK PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Muryati Muryati; Ira Vahlia; Nurul Farida (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The aims of this study were to (1) determine the implementation of ICARE-based e-module development supported by FlippingBook in SPLDV material, (2) ensure the feasibility and practicality of the product developed. The research was conducted at SMPN 4 Abung Timur. The type of research used is development and the model used is 4D development (Define, Design, Develop, Disseminate). The data obtained in the research process are qualitative data and quantitative data. The instruments to collect data used were interview forms, validation questionnaires, and student response questionnaires. Based on expert validation, the e-module is categorized as very feasible with a large percentage of 85%. Based on the results of the limited trial, the e-module was stated to be very practical with a large percentage of 87.33%. So it can be concluded that the ICARE-based e-module assisted by FlippingBook on SPLDV material is feasible and practical to use for the learning process.